Numerical Simulations of the Flame of a Single Coaxial Injector - Victor P. Zhukov; Markus Feil (International Journal of Aerospace Engineering)
The processes of mixing and combustion in the jet of a shear-coaxial injector are investigated. Two test cases (nonreacting and reacting) are simulated using the commercial computational fluid dynamics code ANSYS CFX. The first test case is an experiment on the mixing in a nonreacting coaxial jet carried out with the use of planar laser induced fluorescence (PLIF). The second test case is an experiment on the visualization of hydrogen-oxygen flame using PLIF of OH in a single injector combustion chamber at pressure of 53 bar. In the first test case, the two-dimensional axisymmetric simulations are performed using the shear-stress turbulence (SST) model. Due to the dominant flow unsteadiness in the second test case, the turbulence is modeled using transient SAS (Scale-Adaptive Simulation) model. The combustion is modeled using the burning velocity model (BVM) while both two- and three-dimensional simulations are carried out. The numerical model agrees with the experimental data very well in the first test case and adequately in the second test case.